(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The world is in a continuous state of evolution and during this period, international business operations are the new kid on the block. This, therefore, requires law as a tool of economic engineering to regulate international business processes to ensure productivity without violating international norms and standards. This study aims at evaluating and assessing the impact of law in driving global businesses in the 21st century globalized trade. The implementation of this study will help to assess and redefine the trajectory of the international business community in adjusting to, or adopting new models that can help enhance productivity legally without espousing the world to illicit acts of international kinds. While business experts are keen on the economic theories and models that are required to enhance their financial prowess, the bedrock of the legal basis upon which society thrives – irrespective of whatever society it is – is left in the periphery of international business discourse. In this research, normative legal research is used with extensive literature review to support the theoretical basis of my findings. This research finds that the law should be used as a tool of economic engineering to propel business firms.